Unveiling the fishing history of threatened Brazilian parrotfishes through local ecological knowledge - Queiroz-Véras, Luísa Valentim Melo de Vasconcelos; Ferreira, Beatrice Padovani; de Oliveira, Thais Christina Torres; Véras, Drausio Pinheiro; da Silveira, Camila Brasil Louro; Roos, Natália Carvalho; Landim, Renata Fonseca; Tischer, Marina Consuli; Freitas, Matheus Oliveira; Schiavetti, Alexandre; Hackradt, Carlos Werner; Félix-Hackradt, Fabiana Cézar; et al. (Reviews in fish biology and fisheries, 2025)
Five out of seven Brazilian endemic parrotfish species are classified as threatened, but little is known about the evolution of their fisheries over time and their systematic monitoring is nearly absent. Local ecological knowledge was employed to examine the historical trends in Brazilian parrotfish fisheries and to capture fishers’ perceptions of the current state of these fisheries. In total, 200 interviews were performed in 14 fishing communities in Rio Grande do Norte, Pernambuco and Bahia, in which net, speargun and trap were identified as the three main gears used to harvest parrotfish along the Brazilian coast. The number of weekly fishing trips, along with the time spent and depths explored using nets and spearguns, remained consistent over time, while fishing efforts involving traps increased throughout the years. Nevertheless, the size of fishing grounds and the number of fishers expanded for all fishing gears and in all communities. With changes in fishing strategies, parrotfish fishing grounds shifted from shallow waters to deeper and/or exploited areas farther from their original landing sites, yet total parrotfish catches and CPUEs decreased with time. Sparisoma axillare, Scarus trispinosus and Sparisoma frondosum were the most caught species and presented similar decreasing trends in catches for all states and fishing gears investigated. In addition, the weight of Scarus trispinosus individuals captured by nets and spearguns also decreased. Following the declining trends, most fishers perceived the parrotfish fishery status as worse, regardless of the fishing gear used or their level of experience. Our results are congruent with abundance decreases of the most fished species within only 50–70 years of intensive fishing, a pace faster than that previously registered for any parrotfish species. The Recovery Plan for Brazilian parrotfish is currently under review and the findings presented here should guide and support the collaborative development of new management strategies alongside local fishing communities. Graphical abstract